Massive Trauma in A Community Exposed to Asbestos: Thinking and Dissociation among the Inhabitants of Casale Monferrato. (21st August 2015) - Borgogno, Francesca Viola; Franzoi, Isabella Giulia; Barbasio, Chiara Paola; Guglielmucci, Fanny; Granieri, Antonella
<x xml:space="preserve">Abstract</x> In Casale Monferrato, asbestos exposure has been a traumatic occurrence that has caused cancer and death among the town's inhabitants, resulting in the loss of trust and hope with regard to the future and the loss of healthy aspects of the self. This traumatic history has been denied for many years – part of an 'out of sight, out of mind' attitude that is often justified by financial interests. When traumatization is due to the careless behaviour of the owners of the major economic resources in a community, group identity is deeply affected. In such a situation, psychoanalytic group therapy seems to be the best means to historicize the event and create multiple narratives of somatopsychic suffering. In this paper, we present the experience of the first multifamily group in Casale Monferrato, focusing on the possibility of 'diluting' transference‐ and countertransference‐related feelings of helplessness, thereby making them more bearable and thinkable. Sharing the meaning of the trauma also highlighted vital aspects in the functioning of the mind of the group, leading to a new and more mature way of facing illness and death.